2020
DOI: 10.5114/hm.2021.101757
|View full text |Cite
|
Sign up to set email alerts
|

Notational analysis of beach handball

Abstract: PurposeOne factor affecting successful performance in beach handball is the efficiency of shootings. As only few studies evaluated gender-related differences in shooting performance, the aim of this study was to analyse variations of shooting efficiency between males (M) and females (F) during beach handball matches.MethodsNine matches were analysed. Overall, there were 559 (M: 353; F: 206) shots, of which 54.7 ± 9.4% were successful and 19.9 ± 7.1% were goalkeepers’ saves. Type of shot, shooting area, and goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…in relation to the previous feature, it seems that men had more chances to score than women in beach handball. Given that there was a greater frequency of spin shots for both genders in the 2014 competition [26,27], and also in European youth teams [12] and in a specific tournament [16], although the spectacular goal can be performed in different ways (e.g. 360° spin shot, in-flight shot, penalty shot, shot by a goalkeeper or specialist player) [28], the fact that men were more effective may be explained by differences in strength of lower and upper limbs between genders or by the level of training [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in relation to the previous feature, it seems that men had more chances to score than women in beach handball. Given that there was a greater frequency of spin shots for both genders in the 2014 competition [26,27], and also in European youth teams [12] and in a specific tournament [16], although the spectacular goal can be performed in different ways (e.g. 360° spin shot, in-flight shot, penalty shot, shot by a goalkeeper or specialist player) [28], the fact that men were more effective may be explained by differences in strength of lower and upper limbs between genders or by the level of training [29].…”
Section: Discussionmentioning
confidence: 99%
“…they demonstrated that the winning teams performed a greater number of in-flight goals more effectively than the losing teams. iannaccone et al [16] investigated the efficiency of shots in beach handball (semifinal and final matches of senior, U18, and U12 teams), comparing male and female teams, and reported that no significant gender differences emerged for the different types of shots, shooting areas, or goal areas.…”
Section: Introductionmentioning
confidence: 99%
“…En estudios sobre balonmano playa, coincide con lo expresado por los entrenadores según lo relevado por Silva y Menezes (2018). Se destaca, en relación al estudio de Iannaccone et al (2020) que los lanzamientos efectuados desde la propia área de portería por parte de la portera, aparecen en mayor proporción que los registrados en el estudio de una de las fases del European Beach Handball Tour (Calise Cup). La zona de más lanzamientos fue la zona central interior, seguida por la zona lateral interior izquierda.…”
Section: Discusión A) Distribución De Los Lanzamientos Y Su Culminaci...unclassified
“…Sin embargo, en el torneo absoluto Europeo 2017 la eficacia en los lanzamientos con giro fue mayor en hombres comparado con mujeres (Zapardiel, 2018a). Iannaccone, Fusco, Conte & Cortis (2020) encontraron que la eficacia de lanzamiento fue de mayor a menor según fue ejecutado a través de in-flight, con giro o del especialista respectivamente.…”
Section: Introductionunclassified
“…The relative workload of team handball is about 70–80% of the maximal oxygen uptake (VO 2 max), and the total distance covered per full-time match (60 min) ranges between 3900 to 4700 m, of which about 700 to 1500 m are related to the strategic/technical changes mentioned above [ 1 , 2 , 6 ]. Physical demands differ between elite and lower-level players, and also depend on playing court [ 7 , 8 , 9 ] and playing positions, with wing players performing faster breaks, and backcourt players and pivots experiencing more physical impacts with opponent players [ 1 , 2 ]. Thus, physical characteristics that are dictated both by genetics and training stimuli [ 10 , 11 , 12 , 13 ] influence playing performance since they are highly related to the playing positions [ 2 , 14 ] and competitive level in both males [ 15 ] and females [ 16 ].…”
Section: Introductionmentioning
confidence: 99%